Analisis Total Quality Service Terhadap Kepuasan Mahasiswa Universitas Kutai Kartanegara Tenggarong - Johansyah Johansyah (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
This research do analysis of the relationship among Tangibles Service Quality(X1), Reliability (X2),Responsiveness (X3) Assurance (X4), Empaty (X5) with satisfaction (Y) students in University of KutaiKartanegara. The research object is treated to the University of Kutai Kartanegara with all ofstudents from the whole faculties in University of Kutai kartanegara as respondents. According toanalysis result which is done, It’s gotten the regression equation Y=4,334 - 0,097X1 - 0,022X1X2 - 0,195X3 - 0,132X4 + 0,258X5